Comparative study of diurnal and nocturnal sap flow of Quercus ilex and Phillyrea latifolia in a Mediterranean holm oak forest in Prades (Catalonia, NE Spain) - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (Trees, 2012)
Droughts are a cyclical disturbance in Mediterranean ecosystems and climate change models forecast an increase of their frequency and severity. Some experimental and observational studies have shown that cooccurring species may cope with drier conditions with different strategies and present different responses. Here, we investigate sap ﬂow response to drought in order to explain the observed differential growth and mortality of Quercus ilex and Phillyrea latifolia at Prades Holm oak forest (NE Spain). We measured sap ﬂow of these species and compared their diurnal, nocturnal and seasonal patterns and their relationship with environmental variables. Both species described qualitatively similar daily patterns, either during daylight or night. Sap ﬂow rates were signiﬁcantly higher in P. latifolia except in autumn and spring. P. latifolia was more sensitive to soil moisture. Nocturnal sap ﬂow was detected in both species with no signiﬁcant differences and hourly rates suffered a progressive increase from 3 a.m. to dawn in most sampled nights. Our results indicate a better adaptation of P. latifolia to this site as it can take better advantage of wet periods while maintaining higher sap ﬂow rates during dry periods. Along with previous ecophysiological studies at the same location it may be inferred that at its drier distributional limit Q. ilex would be at disadvantage with respect to other species like P. latifolia, as the latter would cope better with increasing xeric conditions already occurring and further predicted for Mediterranean ecosystems. Our results also show nocturnal sap ﬂow to be relevant in individual water losses in these two species as they can be up to 35–40 % of daily sap ﬂow. Further research on the underlying mechanisms of this nocturnal sap ﬂow is required since it may also enhance early morning CO2 ﬁxation or nutrient supply to leaves.
Keywords: á; Drought; ilex á sap flow; nocturnal sap flow; nocturnal sap flow á; phillyrea latifolia; phillyrea latifolia á quercus; Quercus ilex; sap flow

Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Angulo, Elena; Caut, Stéphane; Cerdá, Xim (Biological Invasions, 2011)
Above-ground invertebrates may represent a high proportion of animal biomass, but few data are available on their fate after death. In Mediterranean ant communities, they are frequently scavenged by ants. Here, we assessed the consequences of Argentine ant invasion on the removal of arthropod corpses in Don˜ana National Park (SW Spain). In three natural habitats that differed in their degree of vegetation cover (i.e. protection for ants against high temperatures), we experimentally provided dead Drosophila, and observed their disappearance over a 60-min period at different times of day and year. The habitats used were isolated cork oak trees, pine tree forest and dry scrubland; we compared invaded with uninvaded plots in each. Oak trees were the most invaded habitat, while scrubland was the least and the only one where the Argentine ant coexisted with native ant species. In accordance with this degree of invasion, the Argentine ant removed the highest percentage of dead ﬂies in oak trees and the lowest in scrubland. Its performance as scavenger was higher than uninvaded ant communities, but it was reduced at high temperatures, when native species were highly efﬁcient. The saturated distribution of the Argentine ant colony seems to be the key to its efﬁciency. We discuss how the occurrence and scavenger efﬁciency of the Argentine ant could affect the nutrient cycling and the progression of its invasion.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: á; Ant communities; Arthropod corpses; Doñana; Linepithema humile; linepithema humile á don; Temperature; temperature á ant communities

Microbial C, N and P in soils of Mediterranean oak forests: influence of season, canopy cover and soil depth - Aponte, Cristina; Marañón, Teodoro; García, Luis V. (Biogeochemistry, 2010)
In Mediterranean ecosystems the effect of aboveground and belowground environmental factors on soil microbial biomass and nutrient immobilization-release cycles may be conditioned by the distinctive seasonal pattern of the Mediterraneantype climates. We studied the effects of season, canopy cover and soil depth on microbial C, N and P in soils of two Mediterranean forests using the fumigation-extraction procedure. Average microbial values recorded were 820 lg C g -1 , 115 lg N g -1 and 19 lg P g -1 , which accounted for 2.7, 4.7 and 8.8% of the total pools in the surface soil, respectively. Microbial N and P pools were about 10 times higher than the inorganic N and P fractions available for plants. Microbial C values differed between forest sites but in each site they were similar across seasons. Both microbial and inorganic N and P showed maximum values in spring and minimum values in summer, which were positively correlated with soil moisture. Signiﬁcant differences in soil microbial properties among canopy cover types were observed in the surface soil but only under favourable environmental conditions (spring) and not during summer. Soil depth affected microbial contents which decreased twofold from surface to subsurface soil. Microbial nutrient ratios (C/N, C/P and N/P) varied with seasons and soil depth. Soil moisture regime, which was intimately related to seasonality, emerged as a potential key factor for microbial biomass growth in the studied forests. Our research shows that under a Mediterranean-type climate the interaction among season, vegetation type and structure and soil properties affect microbial nutrient immobilization and thus could inﬂuence the biogeochemical cycles of C, N and P in Mediterranean forest ecosystems.
Keywords: á; dynamics á; Microbial biomass; microbial biomass á nitrogen; nitrogen; Nutrient immobilization; nutrient immobilization á phosphorus; phosphorus; Plant; Plant–soil interactions; seasonal dynamics; soil interactions á seasonal; vegetation cover

N2O and CH4 fluxes in undisturbed and burned holm oak, scots pine and pyrenean oak forests in central Spain - Inclán, Rosa; Uribe, Carla; Sánchez, Laura; Sánchez, Dolores M.; Clavero, Ángeles; Fernández, Ana María; Morante, Ramón; Blanco, Alfredo; Jandl, Robert (Biogeochemistry, 2010)
We investigated N2O and CH4 ﬂuxes from soils of Quercus ilex, Quercus pyrenaica and Pinus sylvestris stands located in the surrounding area of Madrid (Spain). The ﬂuxes were measured for 18 months from both mature stands and post ﬁre stands using the static chamber technique. Simultaneously with gas ﬂuxes, soil temperature, soil water content, soil C and soil N were measured in the stands. Nitrous oxide ﬂuxes ranged from -11.43 to 8.34 lg N2O–N m -2 h -1 in Q.ilex, -7.74 to 13.52 lg N2O–N m -2 h -1 in Q. pyrenaica and -28.17 to 21.89 lg N2O–N m -2 h -1 in P. sylvestris. Fluxes of CH4 ranged from -8.12 to 4.11 lg CH4– C m -2 h -1 in Q.ilex, -7.74 to 3.0 lg CH4 –C m -2 h -1 in Q. pyrenaica and -24.46 to 6.07 lg CH4–C m -2 h -1 in P. sylvestris. Seasonal differences were detected; N2O ﬂuxes being higher in wet months whereas N2O ﬂuxes declined in dry months. Net consumption of N2O was related to low N availability, high soil C contents, high soil temperatures and low moisture content. Fire decreased N2O ﬂuxes in spring. N2O emissions were closely correlated with previous day’s rainfall and soil moisture. Our ecosystems generally were a sink for methane in the dry season and a source of CH4 during wet months. The available water in the soil inﬂuenced the observed seasonal trend. The burned sites showed higher CH4 oxidation rates in Q. ilex, and lower rates in P. sylvestris. Overall, the data suggest that ﬁre alters both N2O and CH4 ﬂuxes. However, the magnitude of such variation depends on the site, soil characteristics and seasonal climatic conditions.
Keywords: á; fire; greenhouse flux á fire; Greenhouse ﬂux; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; quercus pyrenaica á pinus; Soil temperature; soil temperature á; Soil water content; soil water content á; sylvestris á

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions. I: a case study of leaf development and seasonal variation of photosynthetic capacity in Quercus robur (L.), Q. ilex (L.) and their semidecidu - Both, Holger; Brüggemann, Wolfgang (Trees, 2009)
Leaf development of Quercus robur (deciduous), Q. ilex (evergreen) and of their hybrid Q. 9 turneri was assessed under Central European climate conditions. In all three taxa, development of maximum photosynthetic capacity was slow, although whole chain electron transport, grana development, the xanthophyll cycle and the biochemical capacity for photosynthesis were already completely present at day 7 after budbreak (DAB 7). In the course of the following 30 days, shifts in the levels of metabolites of the photosynthetic dark reactions were observed, indicating a change from ribulose bisphosphate (RubP) regeneration limitation towards RubP consumption limitation of photosynthesis. At the same time, electron transport rates had strongly increased and the capacity of the light reactions did not seem to limit photosynthesis. Sucrose levels in the leaves increased strongly, indicating sink limitation of photosynthesis, which might be responsible for the observed slow development of maximum photosynthetic capacity in all three taxa.
Keywords: á; leaf development; leaf development á quercus; photosynthesis; Quercus; Sink limitation; sink limitation á photosynthesis

Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) - Silva, Pedro Martins; Aguiar, Carlos a. S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M.; da Silva, Pedro Martins; Aguiar, Carlos a. S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M. (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.
Keywords: á; agro-forest mosaic; agro-forest mosaic á biodiversity; Biodiversity conservation; conservation á epigaeic coleoptera; epigaeic coleoptera; indicator value; indicator value á land-use; intensification á quercus suber; land-use intensification; Quercus suber

Cork-oak woodlands as key-habitats for biodiversity conservation in Mediterranean landscapes: a case study using rove and ground beetles (Coleoptera: Staphylinidae, Carabidae) - Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M.; da Silva, Pedro Martins; Aguiar, Carlos a S.; Niemelä, Jari; Sousa, José Paulo; Serrano, Artur R. M. (Biodiversity and Conservation, 2008)
Land-use intensiﬁcation in Mediterranean agro-forest systems became a pressure on biodiversity, concerning particularly the woodland sensitive species. In 2001, the effects of a land-use gradient from old-growth cork-oak forest to a homogeneous agricultural area were assessed using rove beetles as indicators in a Mediterranean landscape. The aim was to ﬁnd which species were negatively affected by land-use intensiﬁcation at the landscape level and whether they beneﬁted from cork-oak patches occurring along the land-use gradient. A total of 3,196 rove beetles from 88 taxa were sampled from all landscape types. Agricultural area recorded signiﬁcantly higher numbers of abundance and species richness in relation to the cork-oak mosaics, i.e. the old-growth forest and the managed agro-forest landscapes (montados). Moreover, 70% of rove beetle indicator species common enough to be tested by IndVal displayed their highest indicator value for agriculture, showing a lower number of woodland indicators in comparison to ground beetles. Nevertheless, one rove beetle taxon was considered a specialist of closed woodland mosaics while no specialist ground beetle was found for that landscape typology. Some rare rove beetle species were also important in typifying diversity patterns of oldgrowth cork-oak forests. Hence, future management in Mediterranean landscapes should take into account not only indicator species common enough to be tested by IndVal, but also rare and endemic species. Considering the added value of cork-oak woodland cover for sensitive rove and ground beetle diversity, the strengthening of cork-oak woodland connectivity seems to be a crucial management that is required in agricultural Mediterranean landscapes.
Keywords: á; agro-forest mosaic; agro-forest mosaic á biodiversity; Biodiversity conservation; conservation á epigaeic coleoptera; epigaeic coleoptera; indicator value; indicator value á land-use; intensification á quercus suber; land-use intensification; Quercus suber

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid